Exploring the behavior of online fitness users by using the Unified Theory of Acceptance and Use of Technology - Hsu, Chi-Yueh; Wang, Ming-Yueh; Lee, Ting-I; Chiang, Hsiu-Hui; Chien, Chun-Yu (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to explore the behavior of online fitness users by using an integrated technology acceptance model. We also discussed the significant impact of fitness live streaming users on the integrated technology acceptance model. A cross-sectional study was carried out on a sample of 150 users who used Facebook fitness live streaming platform to watch fitness live streaming videos and used the live message reply, like and tracking functions. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was utilized to examine the behavior of users of Facebook fitness live streaming platform. The results showed that there are statistically significant impacts in each structure of UTAUT, and the users of fitness live streaming have positive effects in UTAUT. In addition, the convenience and the infinity of Internet allows the social media users to obtain effective information through fast and real-time communication media and most users have the resources and knowledge required for live streaming.